Catheter ablation of atrial fibrillation in patients with left bundle branch block - Tang, Ri‐Bo; Lv, Wen‐He; Long, De‐Yong; Dong, Jian‐Zeng; Du, Xin; Sang, Cai‐Hua; Yu, Rong‐Hui; He, Liu; Jiang, Chen‐Xi; Wen, Song‐Nan; Liu, Nian; Li, Song‐Nan; et al. (Pacing and clinical electrophysiology, 2024)
Left bundle branch block (LBBB) and atrial fibrillation (AF) are commonly coexisting conditions. The impact of LBBB on catheter ablation of AF has not been well determined. This study aims to explore the long-term outcomes of patients with AF and LBBB after catheter ablation. Forty-two patients with LBBB of 11,752 patients who underwent catheter ablation of AF from 2011 to 2020 were enrolled as LBBB group. After propensity score matching in a 1:4 ratio, 168 AF patients without LBBB were enrolled as non-LBBB group. Late recurrence and a composite endpoint of stroke, all-cause mortality, and cardiovascular hospitalization were compared between the two groups. Late recurrence rate was significantly higher in the LBBB group than that in the non-LBBB group (54.8% vs. 31.5%, p = .034). Multivariate analysis showed that LBBB was an independent risk factor for late recurrence after catheter ablation of AF (hazard ratio [HR] 2.19, 95% confidence interval [CI] 1.09-4.40, p = .031). LBBB group was also associated with a significantly higher incidence of the composite endpoint (21.4% vs. 6.5%, HR 3.98, 95% CI 1.64-9.64, p = .002). LBBB was associated with a higher risk for late recurrence and a higher incidence of composite endpoint in the patients underwent catheter ablation.